1993
DOI: 10.1177/089033449300900423
|View full text |Cite
|
Sign up to set email alerts
|

Codeine and the Breastfed Neonate

Abstract: Codeine is an analgesic commonly used to relieve pain in the early post partum. Its metabolite, morphine, is probably responsible for its effectiveness in this use. However, morphine may also cause neonatal apnea. We studied free codeine and morphine levels in breastmilk of 17 samples from seven mothers and neonatal plasma of 24 samples from 11 healthy, term neonates. Levels were determined by radioimmunoassay. Milk codeine levels ranged from 33.8 to 314 ng/ml 20 to 240 minutes after codeine; morphine levels r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(28 citation statements)
references
References 9 publications
0
27
0
1
Order By: Relevance
“…Codeine has a milk-to-plasma ratio of slightly more than 1 suggesting it is generally safe (Meny et al, 1993), but morphine toxicity and death has been reported in a breastfed neonate whose mother was an ultra-rapid metaboliser of codeine (Madadi et al, 2008 Level IV). A relationship between infant central nervous system (CNS) symptoms (decreased alertness, lethargy, poor…”
Section: Opioids and Tramadolmentioning
confidence: 99%
“…Codeine has a milk-to-plasma ratio of slightly more than 1 suggesting it is generally safe (Meny et al, 1993), but morphine toxicity and death has been reported in a breastfed neonate whose mother was an ultra-rapid metaboliser of codeine (Madadi et al, 2008 Level IV). A relationship between infant central nervous system (CNS) symptoms (decreased alertness, lethargy, poor…”
Section: Opioids and Tramadolmentioning
confidence: 99%
“…However, there is no published data on analysis of heroin in human breast milk, while two publications reported on the determination of codeine and morphine levels by radioimmunoassay (RIA) [134] and the determination of morphine and its metabolite by LC-UV [135]. With respect to cannabis, Perez-Reyes & Wall quantified for the first time Δ9-tetrahydrocannabinol (THC) in two breastfeeding women [136] but no validation parameters were available.…”
Section: Analytical Methods For Determination Of Licit and Illicit Drugmentioning
confidence: 99%
“…The FDA review3 and LactMed summary4 of the medical literature of data regarding codeine use during breast feeding found numerous cases of excess sedation and respiratory depression in breastfed infants. These reviews reference the early breast milk and newborn plasma assay article36 and have included the above-mentioned case report about a neonatal death (published twice2 37). The mother in the latter case had taken repeated doses of paracetamol combined with codeine for several days.…”
Section: Contraindications For Codeine Should Not Be Applied To Tramamentioning
confidence: 99%